IMPROVING STUDENTS’ SPEAKING SKILL BY USING “CLASS STORY” - Suparlan, Suparlan (LPPM Institut Pendidikan Nusantara Global, 2020)
The research aim is to prove improving students’ speaking skill in MTs. Darul Aminin NW Aikmual in academic year 2019/2020 by using “Class Story” method. The population of this research was the first level students’ of MTs. Darul Aminin NW Aikmual in academic year 2019/2020 and the sample of the students were 25 students. The researcher used a speaking test as the instrument of the research. The instrument of data collection is the test given as pretest and post test. The result of the data indicates that the t-table (2.012) is lower than the t-counted value (9.817) by applying 0.05 level of significance and the degree of freedom (df) is 48 (df=25 + 25 – 2 = 48). It means that the research hypothesis is accepted. It proves that improving students’ speaking skill at the first level of MTs. Darul Aminin NW Aikmual in academic year 2019/2020 can use “Class Story” method.